An imperative to focus the plastic pollution problem on place-based solutions - Hardesty, Britta Denise; Willis, Kathryn; Vince, Joanna (Frontiers in Sustainability, 2022)
There is an increased focus on plastic pollution and the resultant harms in our oceans and on our shores at local, regional, and global scales. New technologies are being developed and trialed, multilateral agreements are coming into play, and the role of a circular economy is increasingly touted as the key to help solve the plastic pollution crisis. Simultaneously, we are witnessing the disruption of global supply chains from the COVID-19 pandemic, increased fuel prices and increased scope and scale of natural disasters. Individual countries are setting national targets and are developing national plans of action to combat plastic pollution. In this paper, we focus on Australia's National Plastics Plan as a case study of a national approach to addressing this transboundary issue. We discuss the Plan in relation to supply chains, the role of standards and best practices, and principles for a successful circular plastic economy. We explicitly consider the role of reverse logistics and regional approaches that could be developed and implemented within island nations. Overall, we argue for culturally appropriate, economically and environmentally place-based solutions as a necessary approach to help reduce plastic losses to the environment, acknowledging that plastics leakage to the environment is a social equity issue.